2006
DOI: 10.1063/1.2390700
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical cluster ensemble analysis of random sphere packings

Abstract: We introduce a geometric analysis of random sphere packings based on the ensemble averaging of hard-sphere clusters generated via local rules including a nonoverlap constraint for hard spheres. Our cluster ensemble analysis matches well with computer simulations and experimental data on random hard-sphere packing with respect to volume fractions and radial distribution functions. To model loose as well as dense sphere packings various ensemble averages are investigated, obtained by varying the generation rules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
2
19
1
Order By: Relevance
“…The spheres have been shown to be random close-packed (RCP) [7]. Wouterse and Philipse [8] tested five RCP algorithms, and showed that two different variations of the "Mechanical Contraction Method" resulted in RCP stackings that were most similar to an experimental stacking. The simpler of those two algorithms, the "Modified Mechanical Contraction Method", was selected [8,9] for our study.…”
Section: Hollow Spheresmentioning
confidence: 99%
See 1 more Smart Citation
“…The spheres have been shown to be random close-packed (RCP) [7]. Wouterse and Philipse [8] tested five RCP algorithms, and showed that two different variations of the "Mechanical Contraction Method" resulted in RCP stackings that were most similar to an experimental stacking. The simpler of those two algorithms, the "Modified Mechanical Contraction Method", was selected [8,9] for our study.…”
Section: Hollow Spheresmentioning
confidence: 99%
“…Wouterse and Philipse [8] tested five RCP algorithms, and showed that two different variations of the "Mechanical Contraction Method" resulted in RCP stackings that were most similar to an experimental stacking. The simpler of those two algorithms, the "Modified Mechanical Contraction Method", was selected [8,9] for our study. After sphere locations were determined, the cylindrical welds were inserted to connect spheres, or overlapping walls were merged.…”
Section: Hollow Spheresmentioning
confidence: 99%
“…9,14,15,25,48 Alternatively, the Delaunay graph of the particle centers 49,50 is used to define NN. 5,20,23,41,51 In this parameterfree method, every sphere which is connected to a sphere a by a Delaunay edge is considered a NN of a. A rarely used definition is to assign a fixed number n f of NN to each particle, n(a) = n f .…”
Section: Ambiguity Of the Neighborhood Definition And Its Effect On Q Lmentioning
confidence: 99%
“…The local structure metrics q l have been used to identify fcc, hcp, bcc or icosahedral structures in condensed matter and plasma physics (e.g., in colloidal particle systems, 4 random sphere packings, 23,34 or plasmas 35 ) by analyzing histograms over the (q 4 , q 6 )-plane or combinations of similar order parameters. 6 Frequently, histograms of one order parameter only, namely, q 6 , are used to qualitatively compare disorder in particulate matter systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation